Minimal focus of adenocarcinoma on prostate biopsy: clinicopathological correlations. Issue 3 (1st March 2003) - Leroy, X; Aubert, S; Villers, A; Ballereau, C; Augusto, D; Gosselin, B
Abstract : Aims: To establish the clinicopathological features of minimal volume prostate adenocarcinoma on prostate biopsy. Methods: Twenty four cases of minimal adenocarcinoma diagnosed on prostate biopsy and treated by radical prostatectomy were reviewed. Results: The major microscopic criteria were nuclear enlargement (22 of 24), infiltrative pattern (19 of 24), prominent nucleoli (19 of 24), intraluminal eosinophilic secretions (15 of 24), and high grade intraepithelial neoplasia associated (11 of 24). Sixteen of 24 cases were assigned a Gleason score 6 on biopsy. When the whole gland was assessed, 22 of these tumours were localised to the prostate (stage pT2), and only two cases were stage pT3. Conclusions: Minimal focus of adenocarcinoma on prostate biopsy is not an uncommon finding. It is usually an intermediate grade and localised stage neoplasm.